Development of management system for D’xpose Fitness Centre Studio / Nursyahirah Hanaldin - Hanaldin, Nursyahirah (2017)
D’xpose Fitness Centre Studio is a fitness centre that provides many types of classes such as Zumba, samaerobics, dance workout, step fit and body cardio, hi-lo aerobic and body turning, bollyfit dance and cardio dance class. This fitness centre also conducts the event that has been offered by the customer. The data of the customer and event need to be recorded to ensure that there is no double booking. This fitness centre accept only one event for one day. The information of participant also recorded in log book and currently there is no health status information for each participant. The total fees that paid by participant is calculated manually by staff. The project that is developed will assist stakeholder and staffs in managing their daily operation since they still using manual system. This project which is a web based system is carried out with an aim to develop the management system for D’xpose Fitness Centre Studio. This project using the three-tier architecture and waterfall model. The waterfall model involved three phases which are gather and analyse the requirement, design and develop the system. As a result, D’xpose Fitness Centre Studio Management System is produced together with documentations of Software Requirement Specification (SRS) and Software Design Document (SDD). For future work, this system can be extended as application which participant and customer can manage their information.